2022
DOI: 10.1126/science.abm1748
|View full text |Cite
|
Sign up to set email alerts
|

Complex morphologies of biogenic crystals emerge from anisotropic growth of symmetry-related facets

Abstract: Directing crystal growth into complex morphologies is challenging, as crystals tend to adopt thermodynamically stable morphologies. However, many organisms form crystals with intricate morphologies, as exemplified by coccoliths, microscopic calcite crystal arrays produced by unicellular algae. The complex morphologies of the coccolith crystals were hypothesized to materialize from numerous crystallographic facets, stabilized by fine-tuned interactions between organic molecules and the growing crystals. Using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 34 publications
1
50
1
Order By: Relevance
“…In spiders, prismatic crystals were proposed to form on sheets within a crystal vesicle( 24 ) and to be comprised of 25 nm-thick crystal lamellas stacks ( 25 ). Studies on inorganic biocrystals suggest that crystal morphogenesis is controlled by physical confinement of growth by the delimiting membrane of the organelle( 26 ). The rationale here being that confinement allows for growth rate manipulations, which are sufficient to produce a variety of complex shapes.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In spiders, prismatic crystals were proposed to form on sheets within a crystal vesicle( 24 ) and to be comprised of 25 nm-thick crystal lamellas stacks ( 25 ). Studies on inorganic biocrystals suggest that crystal morphogenesis is controlled by physical confinement of growth by the delimiting membrane of the organelle( 26 ). The rationale here being that confinement allows for growth rate manipulations, which are sufficient to produce a variety of complex shapes.…”
Section: Figurementioning
confidence: 99%
“…The formation of thin plate-like guanine crystals requires overriding the strong intrinsic tendency of crystals to grow as prisms and to preferentially express the thermodynamically disfavored (100) face (parallel to the H-bonded plane)( 10 ). Recent studies suggest that the control over morphology of certain biocrystals can be obtained via confinement, i.e., a physical block of growth by the delimiting membrane( 26 ). However, we found that the initial crystal formation within the iridosome lumen occurs at a considerable distance from the delimiting membrane.…”
Section: Figurementioning
confidence: 99%
“…Understanding how organisms control the formation of biogenic crystals is the central, widely studied question of (inorganic) biomineralization [1][2][3][4][5][6] . However, the mechanisms underlying the formation of organic bio-crystals, which are ubiquitous in animals [6][7][8][9] and plants 10 , remain a mystery.…”
Section: Introductionmentioning
confidence: 99%
“…Biominerals are crystalline composites formed by living organisms 25,33,34,35,36,37,38,39,40 . Different animals, such as corals, sea urchins, and mollusks diverged from one another 600-800 million years ago (Ma) 3,4 , but started making their biominerals during the Phanerozoic (541 Mapresent), with the oldest fossils of biominerals for these three phyla being 510, 270, and 535 Ma, respectively 3,41,42,43 .…”
Section: Introductionmentioning
confidence: 99%